MENINGKATKAN KETERAMPILAN PROSES DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASISMASALAH PADA MATA PELAJARAN IPASDI SEKOLAH DASAR - Bela Sapitri; Ipinda Intan Saliya; Nenden Nuraini Rizkiah (CV. ADIBA ASIHA AMIRA, 2023)
The purpose of this study was to improve the science process skills of Grade IV students at SD Negeri 139/I Sungai Buluh for the 2022/2023 school year through learning science through the application of the PBL learning model. The form of this research was classroom action research (CPS) which was carried out in three periods. Each cycle consists of two meetings, each of which begins with the stages of planning, implementing, observing and reflecting. The research subjects were teachers of SD Negeri 139/I Sungai Bulu and fourth grade students for the 2022/2023 school year, a total of 33 students. Sources of data come from teachers, students and various documents. Observation, interviews and document review were used as data collection techniques. The validity testing technique used is content validity. Data analysis techniques used include data collection, data reduction, data presentation, and inference. The results of the study show that the Problem Based Learning (PBL) learning model can improve the KPS of Grade IV students at SD Neger 139/I Sungai Buluh for the 2022/2023 academic year.